Development of novel CO2-selective chitosan membrane blended with synthetic amines and natural amines of silk fibroin and sericin - Prasad, Babul (My University, 2019)
The major objective of the present work is to develop a thermally stable biopolymer-based membrane for CO2 separation using facilitated transport mechanism. The biopolymer chitosan (CS) enables facilitated transport of CO2 by dint of the amine group present in its structure, is thermally stable in absence of crosslinking and possess good film forming ability. The CO2 permeance of the CS membrane with poly(ether sulfone) (PES) as a support, was 12.5 GPU and CO2/N2 selectivity was 54 at 90 °C with water flow rate of 0.03/0.05 ml/min (feed/sweep) and absolute pressure of 2/1.21 bar (feed/sweep) for binary gas mixture. The pristine CS membrane proved to be thermally stable under the operating conditions. Hence, the CS membrane was further explored by incorporation of synthetic and natural amines as carriers for improving and facilitating the transport of CO2 gas molecules. There exists only one amine group per monomer of the CS polymer that can act as carrier. In order to increase the total amine content in the active layer, tetraethylenepentamine (TEPA) was blended and the CO2 separation performance was evaluated. The CO2 permeance increased two fold as compared to pure CS membrane to 24.7 GPU and CO2/N2 selectivity reached to 80 by blending 30 wt % of TEPA, at similar operating conditions. The poly(allylamine) (PAA) consists of mainly primary amine groups which is very brittle in the dry state with inability to form stable films alone. The blending of PAA with CS at optimized content of 70 wt % of CS and 30 wt % of PAA (PAA30) resulted in further improvement in the CO2 separation performance. However, CO2 separation with long-term stability, simultaneously with high permeance through eco-friendly and cost-effective materials is of utmost concern.
Mandal, Bishnupada
Keywords: CHEMICAL ENGINEERING